The relationship between the teaching experience of South African geography teachers and their involvement in self-directed professional development activities (The Journal of Geography Education in Africa, 2022)
This study explores the relationship between teaching experience of geography teachers and their involvement in self-directed professional development (SDPD) activities to enhance their geography knowledge, skills and attitudes, understanding and development in the geography curriculum areas, as well as teaching and learning practices. A non-experimental survey design was employed in the study. Grade 10 to 12 geography teachers (n = 130) from the Dr Kenneth Kaunda and Bojanala Platinum districts in the North West province in South Africa with different amounts of teaching experience in geography education who attended the scheduled geography meeting with their respective subject advisors, completed a questionnaire on SDPD activities in geography education, developed by the researcher. The analysis of the results did not establish any relationship between geography teachers’ teaching experience and their involvement in SDPD activities. In this study the practical significance was calculated to indicate whether the difference between the geography teachers with different teaching experiences and their involvement in SDPD activities is large enough to have an effect in practice. Medium to small practically significant differences between early-, mid- and late-career geography teachers’ involvement in reading articles and books, watching videos, consulting role-players and experimentation were reported. Interestingly, medium practically significant differences were reported between mid-career and late-career geography teachers in conducting self-directed research in geomorphology, development geography and geographical information systems.
Keywords: geography teachers; teaching experience; self-directed learning; self-directed professional development activities